Piperazine-2, 5-dione derivatives and an α-pyrone polyketide from Penicillium griseofulvum and their immunosuppression activity. (June 2021) - Zang, Yi; Gong, Yihua; Chen, Xia; Wen, Huiling; Qi, Changxing; Chen, Chunmei; Liu, Junjun; Luo, Zengwei; Wang, Jianping; Zhu, Hucheng; Zhang, Yonghui
Abstract: Four undescribed piperazine-2, 5-dione derivatives designated janthinolides C–F, and an α -pyrone-containing polyketide namely trichopyrone C, were isolated from the extract of the fungus Penicillium griseofulvum along with four known products. Among them, janthinolide C represents the first naturally occured piperazine-2, 5-dione analogue featuring a cleavaged piperazinedione ring with an oxime group, while the structure of janthinolide D possesses a rare N -methoxy group in natural products. Their structures and absolute stereochemistry were elucidated based on spectroscopic data, theoretical NMR and ECD calculations, Snatzke's method, and modified Mosher's method. All compounds were evaluated for in vitro immunosuppression activity in murine splenocytes stimulated by anti-CD3/anti-CD28 mAbs, of which janthinolides B and C showed potential inhibitory activity with IC50 values at 9.3 and 1.3  μ M, respectively. Graphical abstract: Four undescribed piperazine-2, 5-dione derivatives and an α -pyrone-containing polyketide were isolated from Penicillium griseofulvum along with four known compounds. Janthinolide C showed potential immunosuppressive inhibition in murine splenocytes stimulated by anti-CD3/anti-CD28 mAbs with IC50 value at 1.3  μ M. Image 1 Highlights: Four undescribed piperazine-2, 5-diones and an α -pyrone polyketide were isolated from Penicillium griseofulvum. Janthinolide C is the first natural example of piperazine-2, 5-dione comprising a cleavaged piperazinedione ring with a terminal oxime group. Janthinolides B and C showed potential in vitro immunosuppression activity in murine splenocytes stimulated by anti-CD3/anti-CD28 mAbs and no cytotoxicity at the tested concentration.